What can be done to increase future teachers' plant knowledge? - Borsos, Éva; Borić, Edita; Patocskai, Mária (Journal of biological education, 2023)
Plant blindness is becoming a universal phenomenon among both students and adults. They do not know the names of the plants in their immediate environment, nor are they interested in familiarising themselves with the plants that surround them. Teachers and outdoor education can play a vital role in reversing and preventing this phenomenon; however, many teacher-training universities do not believe that this issue is important. Future teachers do not know the names of the plants in their environment, nor are they inclined to hold outdoor classes. This study examines the relevance of outdoor classes in university education as well as the plant knowledge of trainee teachers at universities in three countries, namely Serbia, Hungary, and Croatia. The results show that students who attended classes held in a natural outdoor environment had better plant identification knowledge. Students' plant identification knowledge was found to be at the same level in each of the three countries that were examined.